Analysis of Price and Service Quality’s Impact on the Customer Satisfaction of the Mamikos Application of PT. Mama Teknologi Properti in East Jakarta - Dikson Silitonga (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this era of digitalization, digital marketing strategy is evolving into a new method that is playing an increasingly essential part in marketing business products. This associative quantitative research is intended to see how far price and service quality influence customer satisfaction on Mamikos application of PT. Mama Teknologi Properti in The East Jakarta area. The study population consists of respondents using the Mamikos application of PT. Mama Teknologi Properti in the area of East Jakarta. Also, several methods are used to analyze the data like reliability test, multiple linear regression, validity test, F and T statistical tests. The F test result shows that price and service quality concurrently have a significant effect on Mamikos application’s customer satisfaction based in East Jakarta. Meanwhile, the T test result indicates that the East Jakarta-based Mamikos application’s customer satisfaction is also partially significant impacted by the price and service quality.